THE EFFECT OF PEER TO PEER LENDING, DIGITALIZATION, AND CREDIT RISK ON INDONESIAN BANK PROFITABILITY - Deva Amelia Fatikasari; Edy Supriyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the effect of Peer to Peer Lending, Digitalization Banking, and Banking Credit Risk on the profitability of banking companies as measured by Return on Assets (ROA), with Firm Size and Leverage as control variables. The research object consists of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used purposive sampling, resulting in 161 observations. The analysis method employed is multiple linear regression using SPSS. The results show that Peer to Peer Lending has a positive and significant effect on profitability, Digitalization Banking has a negative and insignificant effect, and Banking Credit Risk has a negative and significant effect on profitability. Meanwhile, the control variables indicate that Firm Size has a positive significant effect, and Leverage has a negative significant effect on profitability. The Adjusted R Square value of 0.514 indicates that the model explains 51.4% of the variation in profitability. This study highlights that fintech factors and financial risks play an important role in influencing banking profitability, although digitalization has not yet provided optimal short-term impacts.